COMPARISON BETWEEN RENOPROTECTIVE EFFECTS OF FEBUXOSTAT AND ALLOPURINOL IN CHRONIC KIDNEY DISEASE PATIENTS WITH HYPERURICEMIA - matta, saksham; Bhutani, Garima; Arora, Tarun; Garg, Renu; rani, seema; Saini, Rahul (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The objective of the study was to compare the renoprotective effects of febuxostat versus allopurinol in chronic kidney disease patients with hyperuricemia. Methods: One hundred and ten patients were divided randomly into two equal groups: group F (febuxostat) and group A (allopurinol). Group F patients received tablet febuxostat 40 mg OD for 4 months and group A patients received tablet allopurinol 100 mg TDS for 4 months. Following parameters such as estimated glomerular filtration (eGFR) assessment, serum creatinine, serum uric acid (SUA), total serum protein, urine creatinine, urine protein, blood urea, and number of dialysis were carried out and repeated at the end of 1st–4th month to check for the effect of the test drugs on the status of kidney function. Observations: Febuxostat caused more rise in eGFR than allopurinol. Meanwhile, the number of patients with eGFR ≤15/mL/min/1.73 m2 showed no difference between the groups. No patient showed >10% decrease in the eGFR values. Febuxostat showed more decline in SUA levels than allopurinol, although the number of patients reaching the target SUA levels was the same in both groups. Febuxostat led to a more reduction in serum creatinine levels than allopurinol. Urine creatinine and urine albumin levels decline were associated more with febuxostat. No remarkable difference in comparison of both the groups in terms of total serum protein and serum globulin, although a significant rise was seen with febuxostat in serum albumin levels. Both drugs had a similar sequel in declining blood urea nitrogen levels. No discernible difference in the number of dialysis sessions needed by patients in the previous month was seen in the study groups. Conclusion: The present study concluded that febuxostat appears to be a better alternative to allopurinol for chronic kidney disease patients with hyperuricemia. Febuxostat has a superior renoprotective effect than allopurinol.